Dilemas e desafios das formas autocompositivas de resolução de conflitos : uma leitura a partir da experiência do Tribunal de Justiça de Pernambuco - Farias, Cleide Márcia de (2014)
This study aims to discuss the application of alternative forms of conflict resolution, specifically mediation and conciliation, and to identify the perception of these figures between service users and operators of Law. The study also seeks to demonstrate that the institutions of mediation and conciliation can promote the fundamental right of access to justice. It also aims, noticing increased attention given to mediation and conciliation held on proceeding pending by the power structures in the judicial sphere. For this purpose presents studies demonstrating the legislative model used in the country for the implementation and application of mediation and conciliation. The paper examines the need for more specific rules to guide the reconciliation, and especially the pre -trial mediation. It also presents statistical data and surveys with the objective of verifying the performance of various forms of conflict resolution used in Brazil, as users become aware of its existence and know the real difference between them. Regarding the technical and methodological procedures, the research involves a literature analysis fundamentally made from books, journal articles and available material on the Internet, documentary, with the analysis of Brazilian legislation, and other countries, about the alternative methods of conflict resolution. The result of the study shows the need for greater disclosure of mediation and conciliation as alternative forms of conflict resolution. Inform and educate people to the various forms that could be used to solve problems from their own ideas and choices, thereby empowering the individual to decide about their own lives and their conflicts, thus representing an instrument of execution citizenship.